ANALISIS FAKTOR-FAKTOR ALIH FUNGSI LAHAN KOPI MENJADI LAHAN CABAI DI DESA SIMPANG SENDER TENGAH KECAMATAN BPR RANAU TENGAH KABUPATEN OKU SELATAN - Imelda, Imelda; Septianita, Septianita; Pusvita, Ema (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study aims to find out what factors influence farmers' decisions in land conversion and how farmers' income after land conversion. The method used in this study is the case study method, the sample units are farmers who are still growing coffee and farmers who have converted their land into chili plants. The method of data analysis to answer the first problem uses logistic regression analysis, while to answer the second problem uses the income formula. Factors that influence coffee farmers' decisions to convert land to chili land are the age of the coffee, number of families, land area and income owned. Meanwhile, the factors that have no significant effect on the coffee farmer's decision to convert land to chili land is the price factor.Keywords: Transfer of Functions, Decisions, Income